High-Throughput Screening of New Antimitotic Compounds Based on CSLabGrid Virtual Organization - Karpov, P.A.; Brytsun, V.M.; Demchuk, O.M.; Pydiura, N.O.; Ozheredov, S.P.; Samofalova, D.A.; Spivak, S.I.; Yemets, A.I.; Kalchenko, V.I.; Blume, Ya.B.; Rayevsky, A.V. (Science and Innovation, 2024)
Within the framework of CSLabGrid virtual organization, the repository of 3-D models of cytoskeletal proteins (tubulins and FtsZ-proteins) has been created using Grid calculations. The repository of structures of canonical anti-microtubule compounds (inhibitors of tubulin polymerization) as well as library of ligands suitable for high-throughput screening (HTS) in Grid has been developed. Having screened the library, 1,164 compounds that demonstrated an elevated affinity with tubulin molecules: 205 to α-tubulin and 959 to β-tubulin are selected. Among 2,886 compounds synthesized at the Institute of Organic Chemistry of the NAS of Ukraine, 6 ones have been established to be promising inhibitors of α- and β-tubulin polymerization in such human pathogens as Pneumocystis carinii, Giardia intestinalis Ajellomyces capsulatus, Ajellomyces capsulatus, Neosartorya fumigata and Candida albicans. These compounds have been recommended for subsequent experimental evaluation of their biological activity as new pharmacological agents.